The image of the world transmitted by maps: notes for a cartographic literacy - Lestegás, Francisco Rodríguez (2023)
As a theoretical-methodological procedure of an inductive nature, this paper holds that maps are social constructions that transmit ideological, cultural, and political messages; therefore, the intention of the cartographic language becomes an item of main interest. It is clear that both people and organizations have always used planispheres for their own purposes, without considering the technical criteria regarding accuracy that are usually pursued by cartographers. Maps are selective and partial representations of territory, so their use cannot escape from personal prejudices or political manipulation. There is no doubt that maps are a fundamental tool in geographical explanation and, therefore, a basic instrument for geographers’ daily work. It is also a widely used resource in the teaching of geography, usually very disconnected from an authentic geographic education. The paper defends that geographic education has to take on the task of promoting geographic literacy, focused on spatial literacy. In particular, Geography is the school discipline that assumes the responsibility of contributing to the development of spatial thinking or reasoning through cartographic literacy.